„Jupiter and Beyond the Infinite”. 2001: Odyseja kosmiczna Stanleya Kubricka - Kozłowski, Krzysztof (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2020)
The article deals with the relationship between film and painting, as well as the sciences (physics, cosmology) of the 20th century. It introduces the historical context important for the time when Kubrick’s film was made, and addresses the issue of abstraction in cinema, contemporary painting and cosmology, confronting artistic and scientific ideas (the models of the Universe). The starting point for the detailed analysis was “autonomous abstract film” (Alicja Helman), which as a film inside a film combines various cinematic types and genres. The analysis of takes and sequences of this film inside a film made it possible to decipher the director’s idea, which is expressed in intra-film references. The particular results of the research were compared with the possible iconographic context (Gerhard Richter). The inclusion of a diagnosis obtained on the basis of materials examined in the Kubrick Archives in London (Kamil Kościelski), and references to cultural tradition (Plato), supplement the aforementioned considerations in an important way.